2015
DOI: 10.1108/jcp-04-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Child homicide: generating victim and suspect risk profiles

Abstract: Purpose -In England and Wales, on average one child every week is a victim of homicide. The purpose of this paper is to explore whether different victim risk profiles and suspect variables can be differentiated for specific victim ages.Design/methodology/approach -This paper presents a preliminary analysis of more than 1000 child homicides committed in England and Wales between 1996 and 2013, from data provided through the Homicide Index. Statistical techniques such as cluster analysis were used to identify sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Research has shown that homicidal biological parents are inclined to use methods that hasten death (for example, smothering or gun-shot trauma), whereas homicidal stepparents more often are motivated by anger and resentment and thus often resort to beating or bludgeoning (Daly & Wilson, 1994;Weekes-Shackelford & Shackelford, 2004). Finally, it can be noted that the predominance of filicide victims in the younger age groups is well in line with results from studies conducted in other countries and other periods (Jason, 1983;Putkonen, Amon, et al, 2009;Roach & Bryant, 2015).…”
Section: Study Vsupporting
confidence: 71%
“…Research has shown that homicidal biological parents are inclined to use methods that hasten death (for example, smothering or gun-shot trauma), whereas homicidal stepparents more often are motivated by anger and resentment and thus often resort to beating or bludgeoning (Daly & Wilson, 1994;Weekes-Shackelford & Shackelford, 2004). Finally, it can be noted that the predominance of filicide victims in the younger age groups is well in line with results from studies conducted in other countries and other periods (Jason, 1983;Putkonen, Amon, et al, 2009;Roach & Bryant, 2015).…”
Section: Study Vsupporting
confidence: 71%
“…Research has shown that filicidal biological parents are inclined to use methods that hasten death (e.g., smothering or gunshot trauma), whereas filicidal stepparents more often are motivated by anger and resentment and thus often resort to beating or bludgeoning . Finally, it can be noted that the predominance of filicide victims in the younger age‐groups is well in line with results from studies conducted in other countries and other periods .…”
Section: Discussionsupporting
confidence: 76%
“…Most previous studies on risk factors for child homicide have focused on offender characteristics, for example, the presence of mental disorder or substance use . Consequently, there is a paucity of research on risk factors directly associated with the victim, although novel cluster analysis‐based efforts have been proposed to advance knowledge regarding victim risk profiles . Nonetheless, a Swedish study has found multiple birth to be an independent risk factor for filicide , though the finding should be interpreted cautiously in view of the small number of cases included.…”
mentioning
confidence: 99%
“…Routine activities theory suggests that three elements are present when victimisation takes place: motivated offenders, suitable targets and an absence of guardianship to protect the victim (Cohen and Felson, 1979). Together, these theories suggest that young children face a greater risk of violence from intrafamilial perpetrators, and that when children begin to spend time outside the home and attend school, they face a higher risk from extrafamilial perpetrators (Boudreaux et al, 2001; Roach and Bryant, 2015).…”
Section: Explaining Child Homicidementioning
confidence: 99%